Desistance and the micro-narrative construction of reformed masculinities in a Danish rehabilitation centre. (February 2016) - Søgaard, Thomas Friis; Kolind, Torsten; Thylstrup, Birgitte; Deuchar, Ross
Juvenile justice systems and reformatory institutions hold the potential to help young offenders and drug abusers change their behaviours and life-courses. Driven by an ambition to pave new ways to examine the inner workings of reformatory institutions this study explores how young male offenders' gendered identities are engaged in a Danish reformatory programme. In recent years existing research on the gendered aspects of reformatory interventions has highlighted how reformatory institutions at times work to promote desistance by problematizing offenders' and drug-abusers' performance of hyper-masculinity and by constructing therapeutic spaces where men can reformulate softer versions of masculinity. Contributing to this line of research, this study explores and discusses how reformatory programmes at times also utilize hyper-masculine symbolism and imaginaries to encourage young offenders and drug abusers to engage in narrative re-constructions of identities and to socialize these into new subject positions defined by agency, self-responsibility and behavioural changes.